(untitled) (Research, Society and Development, 2020)
The use of betaine associated or not with choline chloride 70% in Japanese quail diets in the laying phase was evaluated. 504 Japanese quails (Coturnix cortunix Japonica) were used from 104 to 208 days old, in a 3x2 + 1 factorial design, completely randomized design, seven treatments, nine replications, eight birds per experimental unit. Betaine was supplemented in 20% of the digestible methionine level of the control diet, in diets with reformulated betaine the level of enrichment was in the nutritional matrix of the product (100%) and with an extra recovery of 5% (105%). Choline chloride was fixed at 0.07%. Productive performance, egg quality, histometry, and the number of goblet cells from the duodenum and hepatic glycogen were analyzed. The use of betaine promoted greater weight of the eggs to the control, regardless of the mode of use, the use of choline promoted a superior result in the weight of the eggs. In egg quality, only shell percentage was influenced. The use of the reformulated betaine 100% of the matrix promoted greater height of the villi, and a lower villus: crypt ratio to the treatment with the reformulation enriched by 105%. Hepatic glycogen was not influenced. In goblet cells, the reformulation in an extra 105% of the matrix was superior to the matrix in 100%. The hill reduced villus height, improved villus: crypt ratio, and number of goblet cells. In conclusion, the reformulated betaine enriched in an additional 5% of its nutritional matrix replaces the use of choline chloride in the laying of Japanese quail diets.